\(2.|x-2|+|1-2x|=8\)
Giúp mình nha
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: \(=\dfrac{1}{\sqrt{2}}\cdot\left(\sqrt{2x-2\sqrt{2x-1}}-\sqrt{2x+2\sqrt{2x-1}}\right)\)
\(=\dfrac{1}{\sqrt{2}}\left(\left|\sqrt{2x-1}-1\right|-\left|\sqrt{2x-1}+1\right|\right)\)
TH1: x>=1
\(A=\dfrac{1}{\sqrt{2}}\left(\sqrt{2x-1}-1-\sqrt{2x-1}-1\right)=-\sqrt{2}\)
TH2: 1/2<=x<1
\(A=\dfrac{1}{\sqrt{2}}\left(1-\sqrt{2x-1}-\sqrt{2x-1}-1\right)=-\sqrt{4x-2}\)
2:
\(=\sqrt{x-1+6\sqrt{x-1}+9}-\sqrt{x-2-2\sqrt{x-2}+1+3}\)
\(=\sqrt{x-1}+3-\sqrt{\left(\sqrt{x-2}-1\right)^2+3}\)
4 ( x + 1 )^2 + ( 2x - 1 )^2 - 8 ( x - 1 ).( x + 1 ) = 11
<=>4.(x2+2x+1)+(4x2-4x+1)-8.(x2-1)=11
<=>4x2+8x+4+4x2-4x+1-8x2+8=11
<=>4x+13=11
<=>4x=-2
<=>x=-1/2
=>\(\frac{1}{2}\left(\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{6}+...+\frac{1}{2x-2}-\frac{1}{2x}\right)=\frac{1}{8}\)
=>\(\frac{1}{2}\left(\frac{1}{2}-\frac{1}{2x}\right)=\frac{1}{8}\)
=>\(\frac{1}{2}-\frac{1}{2x}=\frac{1}{4}\)
=>\(\frac{1}{2x}=\frac{1}{4}\)
=> \(2x=4\)
=> \(x=2\)
1) (x+3)(x2- 3x + 9) = x3 + 27
2) (x2 + 2y)2 = x4 + 4xy + 4y2
3) (2x-3)(2x+3) = 4x2 - 9
4) (x + 3y)3 = x3 + 9x2y + 9xy2 + y3
5) (2x2- y)3 = 8x6 - 6x4y + 6x2y2 - y3
6) (x-3y)(x2 + 3xy +9y2)= x3- 27y3
7) (2x + 3y)(4x2 - 6xy +9y2)= 8x3 + 27y3
8) (3x - y2)2= 9x2 - 6xy2 + y4
Bài 1:
a) Ta có: \(x\left(x^2-4\right)=0\)
\(\Leftrightarrow x\left(x-2\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\\x=-2\end{matrix}\right.\)
Vậy: \(x\in\left\{0;2;-2\right\}\)
b) Ta có: \(\left(2x-3\right)+\left(-3x\right)-\left(x-5\right)=40\)
\(\Leftrightarrow2x-3-3x-x+5=40\)
\(\Leftrightarrow-2x+2=40\)
\(\Leftrightarrow-2x=38\)
hay x=-19
Vậy: x=-19
Bài 2:
a) Ta có: \(-45\cdot12+34\cdot\left(-45\right)-45\cdot54\)
\(=-45\cdot\left(12+34+54\right)\)
\(=-45\cdot100\)
\(=-4500\)
b) Ta có: \(43\cdot\left(57-33\right)+33\cdot\left(43-57\right)\)
\(=43\cdot57-43\cdot33+43\cdot33-33\cdot57\)
\(=43\cdot57-33\cdot57\)
\(=57\cdot\left(43-33\right)\)
\(=57\cdot10=570\)
1. \(x^2+2y^2+2xy-2y+1=0\)
\(\left(x+y\right)^2+y^2-2y+1=0\)
\(\left(x+y\right)^2+\left(y-1\right)^2=0\)
Có: \(\left(x+y\right)^2\ge0;\left(y-1\right)^2\ge0\)
Mà theo bài ra: \(\left(x+y\right)^2+\left(y-1\right)^2=0\)
\(\Rightarrow\hept{\begin{cases}\left(x+y\right)^2=0\\\left(y-1\right)^2=0\end{cases}}\Rightarrow\hept{\begin{cases}x+y=0\\y-1=0\end{cases}}\Rightarrow\hept{\begin{cases}x+y=0\\y=1\end{cases}}\Rightarrow\hept{\begin{cases}x=-1\\y=1\end{cases}}\)
\(8\left(x-\frac{1}{2}\right)\left(x^2+\frac{1}{2}x+\frac{1}{4}\right)-4x\left(1-x+2x^2\right)+2=0\)
\(\Leftrightarrow8\left[x^3-\left(\frac{1}{2}\right)^3\right]-4x+4x^2-8x^3+2=0\)
\(\Leftrightarrow8x^3-1-4x+4x^2-8x^3+2=0\)
\(\Leftrightarrow4x^2-4x+1=0\Leftrightarrow\left(2x-1\right)^2=0\)
\(\Leftrightarrow x=\frac{1}{2}\)
8(x-1/2)(x^2+1/2x+1/4) - 4x(1-x+2x^2)+2=0
=> 8𝑥^3 − 1 − 8𝑥^3 + 4𝑥2 − 4𝑥 + 2 = 0
=> 4𝑥2 − 4𝑥 + 1 = 0
=> ( 2x - 1 )^2 = 0
=> 2x - 1 = 0
=> 2x = 1
=> x = 1/2